Prevalence and clinical impact of QRS duration in patients with low‐flow/low‐gradient aortic stenosis due to left ventricular systolic dysfunction. (18th February 2014) - Sebag, Frédéric A.; Lellouche, Nicolas; Chaachoui, Najia; Dubois‐Rande, Jean‐Luc; Gueret, Pascal; Monin, Jean‐Luc
<x xml:space="preserve">Abstract</x> Aims To evaluate the prognostic impact of QRS width in patients with low‐flow/low‐gradient aortic stenosis (LF/LGAS). Methods and results Among 88 consecutive patients referred to our institution for LF/LGAS from September 1994 to March 2007, baseline demographic, clinical, echocardiographic, and electrocardiographic data were collected. This population was divided into two groups according to baseline QRS duration (cut‐off QRS ≥130 ms). Follow‐up data, including electrocardiographic evolution and overall mortality, were analysed. The mean follow‐up duration was 3.1 (2.2–6.2) years. In the whole group, 67 patients underwent surgical aortic valve replacement. Forty‐nine patients (56%) had a QRS duration ≥130 ms. Among operated patients, there was no significant change in QRS duration between baseline and latest follow‐up (126 ± 26 ms vs. 131 ± 25 ms; P = 0.82). In addition, wider QRS was a strong independent predictor of overall mortality (hazard ratio 2.20, 95% confidence interval 1.15–4.24; P = 0.027). Conclusion Significant intraventricular conduction disturbances are common in patients with LF/LGAS and do not recover after aortic valve replacement. QRS duration is strongly associated with mortality in this selected population.